The Knowledge of Phra Ruang’s Proverbs in the half of Century (1960-2013) - Tantasit, Radchadaporn (Asia Social Issues, 2020)
This documentary research aims to investigate the Phra Ruang Proverbs or ‘Suphasit Phra Ruang’ in terms of its cognizance as didactic literature in Sukhothai Era.Emphases are placed on four dimensions: historical backgrounds and author biography; essences and didactic values; compositional styles of the 6 pieces and the proverbs’ relationships with other literary works; and social reflections through didactics. The findings indicate that Phra Ruang Proverbs are accumulated from the all Phra Ruang’s didactics intended for Sukhothai citizens. This literary work comprises 6 pieces in total. The proverbs were composed in rhyme starting with the compositional purposes, the didactics, and the praises for those who observed the principles. The didactics cover 3 dimensions of harmonious social coexistence: education, interactions with others in different hierarchical statuses, and daily living.